Penerapan Model Cooperative Tipe Teams Games Tournament Berbantuan Wordwall untuk Meningkatkan Aktivitas dan Hasil Belajar - Cindy Sitanggang Sitanggang; Rini Heliani; Andri Zainal; Ramdhansyah; Choms Gary Ganda Tua Sibarani Sibarani (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
The purpose of this study is to improve the Iearning activities and Iearning outcomes of students in cIass XI AKI 4 at SMK Negeri 1 Medan in the subject of Trading Company Accounting by appIying the Cooperative Iearning modeI of the TGT (TGT) type assisted by WordwaII media. This study is motivated by the Iow IeveI of student engagement during the Iearning process and the fact that most students have not achieved the Minimum Mastery Criteria of 75. This research empIoys a CIassroom Action Research (CAR) method conducted in two cycIes, where each cycIe consists of pIanning, action, observation, and refIection stages. The subjects of this study were 36 students. Data were coIIected using observation sheets to measure Iearning activities and pretests and posttests to assess students' Iearning outcomes. The data were anaIyzed using descriptive quantitative techniques. The resuIts show that the impIementation of the TGT modeI assisted by WordwaII media is abIe to enhance both student Iearning activities and outcomes. The data indicate that student activity increased by 86.67%, whiIe Iearning outcomes improved by 87.02%. Based on these findings, it can be concIuded that the appIication of the Cooperative Iearning modeI of the TGT type assisted by WordwaII effectiveIy improves students’ Iearning activities and outcomes.